Tannin, Protein Contents and Fatty Acid Composition of the Seeds of Some Trifolium L. species from Turkey - Kokten, Kagan; Kocak, Alpaslan; Kaplan, Mahmut; Akcura, Mevlut; Bakoglu, Adil; Bagci, Eyup (Academic Journals Inc, 2011)
The seed oils of seven Trifolium species (Leguminosae) were investigated for their protein, tannin contents and fatty acid compositions. The fatty acid compositions of these seven different species were determined by gas chromatography of the methyl esters of their fatty acids. The seed protein contents were found to be between 23.57 and 36.60%. The seed tannin contents were found to be between 0.77 and 1.73%. The seed oils of Trifolium species contain palmitic and stearic acids as the major component fatty acids, among the saturated acids, with a small amount of myristic, pentadecanoic, arachidic and behenic acids. The major unsaturated fatty acids found in the seed oils were oleic, linoleic and linolenic acids. In this study, Total Saturated Fatty Acids (TSFA) of Trifolium species were between 18.5 and 24.4% while Total Unsaturated Fatty Acids (TUSFA) were between 71.1 and 80.3%. The results revealed that the seed oils of Trifolium species studied with a substantial amount of very long chain fatty acids might have attracted attention because of their value of nutritional, industrial and renewable resources.
Keywords: Biplot; fatty acid composition; protein contents; tannin; Trifolium sp.